Infraestructura hotelera y el desarrollo turístico del cantón Durán - Román Banchón, Ginger Stefanny (2019)
The purpose of this investigation case is to describe how the poor hotel infrastructure affects the tourism development generated by the disinterest of the authorities in the quality of hotel services, as well as the low budget and ignorance of the consumer profile, it is possible to emphasize the objective of this case study is to describe how hotel infrastructure contribute to the tourism development of the Cantón Durán. For which the exploratory, bibliographic and descriptive research methods were used, where deeper and clearer information on the problem could be obtained through the execution of surveys and observation sheet. As a result, the implementation of a feedback system in the hotel establishments of the city is proposed to obtain customer satisfaction and make the necessary changes for their prompt return